Trends in environmental risk and child health research: A bibliometric study, 1990-2022 - Subhojit Shaw; Aparajita Chattopadhyay; Lobsang Tshering Bhutia (Elsevier, 2024)
Background: Worldwide, climate change has significantly contributed to the global burden of disease. Children are among the most vulnerable groups of population bearing the brunt of climate change. To explore the development of research on environmental risk and child health, a bibliometric analysis was conducted encompassing literature from 1990 to 2022. Methods: The study draws upon 6816 published articles related to environmental risk and child health, sourced from the Scopus database spanning the period from 1990 to 2022. The research encompasses several key analyses: trend analysis, country and journal contribution, author contribution using the Bibliometrix R package and co-occurrence analysis was performed using VOSviewer. Results: The study highlights the major contributions of the USA and China. The USA leads in both Single Country Publications and Multiple Country Publications. The International Journal of Environmental Research and Public Health stands out as the primary source, with the highest number of documents in this field. Co-occurrence analysis revealed common clusters of words like children, child health, mental health, adolescence, and physical activity. The keyword network map highlighted climate change, social determinants of health, and resilience as the most emerging research topics. Conclusions: The study highlights the crucial role of environmental factors in influencing child health. The geographical disparities in research output suggest a need for broader research engagement globally, particularly from developing countries, to better address and mitigate the adverse effects of environmental exposures on children's health worldwide.